2013
DOI: 10.1002/acr.22040
|View full text |Cite
|
Sign up to set email alerts
|

High Heritability of Hallux Valgus and Lesser Toe Deformities in Adult Men and Women

Abstract: Objective To estimate heritability of three common disorders affecting the forefoot: hallux valgus, lesser toe deformities and plantar forefoot soft tissue atrophy in adult Caucasian men and women. Methods Between 2002-2008, a trained examiner used a validated foot exam to document presence of hallux valgus, lesser toe deformities and plantar soft tissue atrophy in 2,446 adults from the Framingham Foot Study. Among these, 1,370 participants with available pedigree structure were included. Heritability (h2) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 45 publications
(43 reference statements)
1
23
1
Order By: Relevance
“…HV is one of the most common foot disorders in older Caucasian and African Americans2 8 and has been confirmed to be heritable in our recent publication 16. In this first ever GWAS meta-analysis of HV, we report a set of potentially suggestive SNPs with p values less than 5×10 −6 in male-specific and female-specific analyses.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…HV is one of the most common foot disorders in older Caucasian and African Americans2 8 and has been confirmed to be heritable in our recent publication 16. In this first ever GWAS meta-analysis of HV, we report a set of potentially suggestive SNPs with p values less than 5×10 −6 in male-specific and female-specific analyses.…”
Section: Discussionmentioning
confidence: 66%
“…Pedigree studies have found that 63–90% of individuals with HV report a family history of the condition 13–15. More recently, HV was found to be highly heritable in the Framingham Heart Study (FHS)16 (involving 1370 European descent Caucasian participants from 429 families) and the Korean Healthy Twin Study (involving 1265 East Asian participants and 206 twin pairs) 17. Although these studies suggest that HV may be hereditary, no candidate gene association study or genome-wide association study (GWAS) has been conducted to examine the genetic predisposition of HV.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that most of the study participants in the Korean study comprised those aged between age 39 and 60, the two findings are generally compatible in indicating the importance of genetic contributions to HV deformity. When we further analyzed our data using the same cut-off as was used by Hannan et al (2013;HVA >15 degrees), the heritability estimate increased to 0.63. There could be some possible explanations for this difference of between 0.45 and 0.63.…”
Section: Discussionmentioning
confidence: 99%
“…Because the relatives of clinical cases share gene pools that predispose an increased risk of HV, the heritability of 0.63 might be overestimated. A recent report by Hannan et al (2013), which adopted the criteria of HVA over 15 degrees as determining HV, demonstrated that the overall heritability in a US white population was 0.29, and heritability was increased to 0.45 when it was estimated for those aged between 39 and 60 years. The same study showed that overall heritability of lesser toe deformity was estimated to be 0.54.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation